Determinants of Women’s Empowerment in Kyrgyzstan: The Mediating Role of Women Entrepreneurship - Mamadiev, Bedelbai (BUKETOV BUSINESS REVIEW, 2026)
This study investigates the determinants of women’s empowerment in Kyrgyzstan, focusing on the mediating role of women entrepreneurship. Key determinants analysed include access to finance, technical know-how, and financial literacy. Utilising Structural Equation Modelling (SEM) and a structured survey for data collection, the study gathered responses from women entrepreneurs across various regions of Kyrgyzstan. The findings reveal that technical and technological knowledge is the most critical determinant for enhancing women’s empowerment. Women with greater technical and technological knowledge exhibit higher levels of empowerment. Additionally, there is a significant positive relationship between access to finance and women’s empowerment, indicating that women with better financial access are more empowered. These insights provide a foundation for developing future women’s empowerment programmes and contribute to the broader understanding of women entrepreneurship in developing economies.